Pola Nafkah dan Perkawinan dalam Tradisi Mudik - Saifuddin Saifuddin (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2025)
The tradition of homecoming is understood by Indonesian people as the meaning of returning to their hometown. This tradition occurs once a year before the Eid al-Fitr holiday for Muslims. The homecoming phenomenon is interesting to study from the perspective of population movement from one place to another, from one region to another. This study examines the influence of livelihood patterns and marriage patterns that cause some people to move from one region to another. Through field research with a phenomenological approach, data were collected using observation and in-depth interview methods. Data collection locations were carried out at several departure points for travelers, namely: land transportation terminals, air transportation terminals and train stations. The research findings revealed that generally they work or earn a living not in their hometown or birthplace, so that when the Eid holiday season arrives, they take advantage of going home to celebrate Eid. In addition, in general, homecoming occurs because the husband or wife does not come from the same birthplace, so that when the Eid season arrives, they take turns going home to celebrate Eid either at the husband's or wife's birthplace. Based on distance, the phenomenon of population movement or homecoming occurs at the level of one district/city to another district/city in the same province, from one district/city to another district/city in a different province, and even across countries.